Strategi Departemen PGPA dalam Upaya Penyelesaian Persoalan antara PT. Chevron Pasific Indonesia dan Masyarakat di Zona Merah - Gussman, Suzy Yolanda (LPPM Abdurrab Pekanbaru, 2017)
Today, trends issues faced by public relations are increasingly complex and diverse. It is inevitable that the public relations business grow in an environment and always experiencing the change. The problem faced by the PGPA Department with people in the red zone is one of the many issues that must be faced by the public relations company working on oil and gas. Those engaged in this industry have a role to support the company's objectives in maintaining the continuity of natural resource exploration. That is why the task of public relations in oil and gas company should focus on maintaining stability. The problems in the red zone is not only seen as a security problem on the site area that has authorized the state to the company. However, there is another issue that becomes a chore for the PGPA Department to address these issues proactively before the existence of the company is rated as a